Demographic and macro-morphological evidence for common reed dieback in central Italy. (4th May 2017) - Lastrucci, Lorenzo; Lazzaro, Lorenzo; Coppi, Andrea; Foggi, Bruno; Ferranti, Francesco; Venanzoni, Roberto; Cerri, Martina; Ferri, Valentina; Gigante, Daniela; Reale, Lara
Abstract : Background: Phragmites australis dieback syndrome, recently reported for the Mediterranean basin, features several symptomatic traits among which the clumping habit seems to be one of the most diagnostic. Aims : We evaluated the effect of water depth on the intensity of the clumping habit and evaluated the diagnostic role of other traits. Methods : We investigated patterns of macro-morphological (culm height and diameter, flowering head and dead apical bud rates) and demographic (density) traits of P. australis in function of submersion (PF-permanent vs. NF-temporary) at five Italian wetland sites. We related the occurrence of clumping and its frequency with water depth. Results : There were clear trends, modulated by site-specific effects, for most of the considered traits in function of the duration of submersion. The clumping rate was close to zero in NF-stands, reached high values in PF-stands and was positively correlated with water depth. Conclusions : We have shown that permanent submersion with deep water levels plays a crucial role in the occurrence of reed dieback. As all other considered traits, with the exception of the occurrence of dead apical buds, well correlate with the clumping habit, we propose using clumping as a key indicator for detecting potential reed dieback.